2011
DOI: 10.5194/aab-54-360-2011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of quarter-individual and conventional milking systems on milkability traits

Abstract: This study was carried out to investigate a new quarter-individual milking system called MultiLactor® (Siliconform GmbH, Türkheim, Germany). The MultiLactor enables milking on quarter level basis with low vacuum (37 kPa), sequential pulsation and periodic air inlet. Within the same dairy farm, the influence of this quarter-individual milking system (MULTI) on milkability traits was compared with a conventional milking system (CON). CON was equipped with a conventional milking cluster and used alternating pulsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Moreover, it has been reported that milk removal is optimal during milking time, when the cows are well prepared and the using milking machine is suitable for the dairy cows requirement (Kanswohl et al 2012) ML milking system was developed and practically used in the field few years ago. The practical results have shown that the using of ML in comparison with the conventional milking systems is more effective in term of positive stimulation effect (Müller et al, 2011). The new study clearly shows the positive influence of the ML milking system on milk yield and composition (kaskous, 2016).…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, it has been reported that milk removal is optimal during milking time, when the cows are well prepared and the using milking machine is suitable for the dairy cows requirement (Kanswohl et al 2012) ML milking system was developed and practically used in the field few years ago. The practical results have shown that the using of ML in comparison with the conventional milking systems is more effective in term of positive stimulation effect (Müller et al, 2011). The new study clearly shows the positive influence of the ML milking system on milk yield and composition (kaskous, 2016).…”
Section: Introductionmentioning
confidence: 76%
“…The evaluation of the AMF results shows that primiparous cows released less milk in the same amount of time than multiparous cows. The slow release of milk after the start of teat stimulation changed during lactation and also depended on the milking interval of the previous milking (Bruckmaier, 2001;Müller et al, 2011). An association between slow milk release and low milk yield has been demonstrated in the study of Erskine et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…More than that, in dairy production, a quarter of the udder is also a typical entity. The advantages of quarter-individual milking are described in the literature [93][94][95][96][97]. This type of milking is available in AMSs as well as in conventional milking parlors [98].…”
Section: State and Potential Of Industry 40 Benefitsmentioning
confidence: 99%